Gambaran Resiko Kehamilan dan Persalinan Pada Ibu Usia diatas 35 tahun di Ruang Kebidanan RSUD Solok Tahun 2017 - Anggraini, Mery Lingga (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Women over the age of 35 years, in addition to physically began to weaken, alsothe possibility of the emergence of various health risks, such as hypertension, diabetesmellitus, and other diseases. Age over 35 years old risk of labor, section of cesaria. Thepurpose of this study was to determine the description of the risk of pregnancy andchildbirth in women aged over 35 years in Midwifery Room RSUD Solok year 2017.This research is descriptive conducted in Midwifery Room RSUD Solok year 2017conducted on 12 June 29017. The population in this study were all pregnant women andmothers aged over 35 years, the sample is 146 respondents with sampling technigue istotal sampling. Data processing through computerized data system is analyzed in the formof univariate analisis.From the results of the study found that pregnant women aged over 35 years a fraction of(23,3%) had preeklamsia, a fraction of (5,0%) had diabetes mellitus, a fraction of (1,7%)had ectopic pregnancy, a fraction of (3,5%) had placenta previa, a fraction of (16,3%) hadabortion, a fraction of (3,5%) had premature birth, a fraction of (4,7%) had BBLR, afraction of (2,3%) had proglonged labor, almost some (39,5%) had cesarian section, morethan half of (63,3%) of mothers had pregnancy at risk, most (84,9%) of mothers had arisky delivery.Is expected for health workers, RSUD Solok counseling team, as well as healthcadres in the field to continue to conduct health counseling on pregnant women and makeefforts to health education and prevention of pregnancy age over 35 years.Keyword : Risk of pregnancy, Child birth